2011
DOI: 10.1002/dvdy.22712
|View full text |Cite
|
Sign up to set email alerts
|

Mutated in colorectal cancer (Mcc), a candidate tumor suppressor, is dynamically expressed during mouse embryogenesis

Abstract: Mutated in Colorectal Cancer (MCC) encodes a multiple PSD‐95/Dlg/ZO‐1 (PDZ) domain‐containing protein implicated, as its name suggests, in the pathogenesis of human colon cancer. To date, however, what role, if any, MCC plays in normal tissue homeostasis and development remains unclear. In an effort to expand our understanding of MCC function and distribution, we examined the expression of the evolutionarily conserved mouse Mcc homolog between embryonic days (E) 6.5 and 12.5 using conventional whole‐mount in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…We previously reported that Mcc null mice are viable and fertile (Young et al, 2011). This dramatic difference between the zebrafish knockdown and mouse loss-of-function phenotypes most likely originates from species-specific differences in early Mcc/mcc expression and/or in the unique cell movements that each organism deploys during gastrulation and formation of the body axis (Solnica-Krezel and Sepich, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that Mcc null mice are viable and fertile (Young et al, 2011). This dramatic difference between the zebrafish knockdown and mouse loss-of-function phenotypes most likely originates from species-specific differences in early Mcc/mcc expression and/or in the unique cell movements that each organism deploys during gastrulation and formation of the body axis (Solnica-Krezel and Sepich, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…1A; supplementary material Table S1). Although two isoforms of Mcc differing only at their extreme N-termini are generated by alternative promoter usage in human and mouse (Young et al, 2011), we were unable to identify an mcc transcript encoding the shorter isoform 2 after exhaustive 5′-RACE and EST database searches. Given the length of the zebrafish Mcc polypeptide, we have therefore provisionally designated it as the longer isoform 1 (supplementary material Table S1).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, an SNP of the MCC gene (rs11283943) is significantly associated with increased risk of breast cancer [28]. Although an inactivating MCC mutation in mice alone failed to induce any evident CRCs, the homozygous mice displayed a slightly higher proliferation rate of the epithelial crypt cells [29,30]. Interestingly, an unbiased genetic screening of a mouse model of CRC implicated MCC mutation as a key event in colorectal carcinogenesis [18].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that during development, MCC is expressed in diverse tissues derived from all three embryonic germ layers, including the developing gut and central nervous system [29]. In adults, MCC is expressed in the surface epithelium of the colon and villi of the small intestines as well as other tissues, including the cerebellar cortex, kidney, pancreas, and liver [31,37].…”
Section: Introductionmentioning
confidence: 99%